The effectiveness of blood donation counseling in increasing blood donation knowledge in high school students in Garut, West Java - Windadari Murni Hartini; Rudina Azimata Rosyidah; M. Imron Mawardi; Balgis Gustian (Universitas Aisyah Pringsewu, 2022)
Blood donation is a voluntary practice of donating blood to be stored in a blood bank and then used for blood transfusions. In Indonesia, blood donation is still a seasonal practice as it is only conducted during certain events. Therefore, health promotion such as counseling is needed to increase public knowledge about blood donation. This study aimed to evaluate the difference in knowledge of donors before and after receiving counseling at SMA Negeri 16 Garut, West Java. This research used a Pre-Experimental method and has not yet become an actual experiment as external variables still affect the formation of dependent variables. The research design used was a One Group Pretest-Posttest Design. The sample was selected using Simple Random Sampling technique with a total of 75 students as respondents. The results showed that before receiving counseling, only 4 respondents had inadequate knowledge of blood donation (0-55%), while 71 respondents had sufficient knowledge of blood donation (56-75%). However, after receiving counseling, knowledge of blood donation increased significantly where all respondents had good knowledge of blood donation (76-100%). The Wilcoxon test showed a significant value of 0.000 (P=0.000 less than 0.05), indicating the influence of blood donation counseling on donor knowledge in SMA Negeri 16 Garut, West Java.